(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The development of theoretical approaches to determining mechanical characteristics of sliding contacts by the creation of a simulation model of a sliding contact with three degrees of freedom and distributed parameters of the transition layer is considered. This model enables to obtain dynamic and integral characteristics of the sliding contact on design parameters given and characteristics of materials of contact pairs.